(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This paper attempts to analyse Amitav Ghosh’s seriousness towards environmental concerns in his novel, The Hungry Tide. The Sundarbans, where land and sea always respect one another, serve as the setting for the novel. Ghosh mainly concentrates on a small-scale culture in the Sundarbans, also known as the tidal country, which are the islets of the Ganges delta that lie east of the fringes of West Bengal/Bangladesh and south of Kolkata. The link between Kanai Dutt and Piyali Roy, two tourists to the Sundarbans, and the tidal nation network is the central theme of the novel. Ghosh has focused more particularly on ecological topics. Kanai, a specialist located in Delhi, travels to see his aunt Nilima, an extremist NGO that operates a guest home, a medical clinic, a philanthropist, and an educational administration on the island. He wants humans to live in harmony with nature by drawing boundaries around these kinds of biologically unfair characters that result from the assaults of human instincts.